Inhibition of Octacalcium Phosphate Crystal Growth by Some Organic Phosphonates - M. Hamza, Salem; M. Gaafar, Eman; A. El Sayed, Fathy; A. Ali, Farag (Asian Journal of Chemistry, 2011)
Phosphonate additives have important applications both in biomineralization processes and in industrial mineral scale formation. The constant composition method has been used to study the influence of some organic phosphonate additives: hydroxyl ethylene diphosphonic acid) (etidronate), alendronate (4-amino-1-hydroxybutylidene) bisphosphonic acid, risedronate (1- hydroxy-2-(3-pyridinyl) ethylidene) bis(phosphonic acid). On the kinetics of crystal growth of octacalcium phosphate (OCP) on octacalcium phosphate seed crystals at pH 6.50 and 37 ºC, ionic strength 0.15 mol L-1 (maintained with NaCl) and an octacalcium phosphate relative supersaturation, σ, of 0.899. Depending upon the Ca/P ratio of the solution, that is equal 1.33. The results indicate that traces of some phosphonates (≤ 10-6 mol L-1) are extremely effective in inhibiting crystal growth. Assuming that the adsorbed additives block discrete growth sites on the crystal surfaces, the kinetic results may be interpreted in terms of a Langmiur adsorption model yielding kinetic affinity constants. The order of inhibitory effectiveness, Alendronate > Risedronate > Etidronate, reflects the ability of the phosphonates to bind to the octacalcium phosphate.